The Correlation Between Carbohydrate Consumption with Blood Pressure Levels of Elderly Communities in Sumbersari Jember - Revin Fiona Cinintya; Dwita Aryadina Rachmawati; Yuli Hermansyah (Faculty of Medicine, University of Jember, 2017)
The increasing population of elderly causes getting more complex illness because impairment in organ function, one of them is the blood vessels. Blood vessels will have decreased nitrite oxide that causes atherosclerosis, as the primary cause of the hypertension. The change of lifestyle and nutrient factor is related to the incident of hypertension. Meanwhile, Indonesians tend to prefer food sources of carbohydrate. The purpose of this research is to analyze relations between consumption of carbohydrate with blood pressure on elderly from active members of Karang Wreda Sriwijaya and Semeru Jaya Sumbersari Jember about 47 samples. This research is an analytic observational research with the cross sectional methods. In this research, samples were interviewed to describe the charracteristic ( the age, sex, the history of hypertension). Then samples were interviewed to know their carbohydrate consumption using 24-hours Food Recall method three times in different time with the maximum of two weeks and the blood pressure was checked with a mercurial sphygmomanometer. The results of this research based on the correlation of Spearman obtained a value of p=0,00 for the number of subject’s carbohydrates consumption with systolic blood pressure and p=0,02 for diastolic pressure. The conclusion is there is a correlation between carbohydrates consumption with systolic and diastolic blood pressure.Keywords: carbohydrates consumption, blood pressure, elderly